Method of constructing logical-event computational models of transforming social information processes - A. Yu. Perevaryukha (Вестник Самарского университета: Естественнонаучная серия)
The article develops a method for organizing a logical-event hybrid model for analyzing socioinformational processes in their stages, event transformations and rapid disturbances. Specific situations with a non-stationary lifetime y of a series of non-overlapping generations are not described by continuous equations of mathematical biophysics. The use of multiparameter functional iterations with the effect of xn+1 = = ψ(r; xn)ξ(a; xn−i) + Θ[n], xmax = max ψ(x) ̸= max ξ(x) leads to a cascade of bifurcations with the coexistence of stable cycles and a set of transition points {ˆr, ˆa} "chaos⇔cycle", which goes beyond the essential interpretation of the trajectory behavior. The proposed method is relevant for modeling cases when y generations have different lengths of juvenile ontogenesis stages. The models are important for forecasting invasive processes of insects capable of mass outbreaks of reproduction, where the factor of generation wintering is in effect. Hybrid structures of equations are constructed that describe the dynamics of generations on adjacent uneven segments of ontogenesis depending on changes in mortality factors due to competition for resources, regulated by the growth rate of organisms. The hybrid model allows one to obtain pulsating dynamics of numbers, where transitions to the state of excessively numerous generations of "outbreaks" are interconnected with the survival of the wintering generation and the level of competitive mortality of the summer generation. The modeling method is relevant for populations supported by artificial reproduction and for cases where different social groups exhibit varying reproductive activity, which is reflected in the development of demographic waves, the disruption of social structures and the disruption of traditional interactions during the crisis of social structures.